EVALUATION OF SOME NOVELS OF HUSEYIN RAHMI GURPINAR FROM THE PERSPECTIVE OF LOVE - Pelin DİMDİK EMEKSİZ (Fırat University, 2020)
41 novels of Hüseyin Rahmi Gürpınar have been published. In this study, 25 novels of the author, which are directly related to the subject, were examined. We determined the views of Hüseyin Rahmi Gürpınar about love from related novels. Thus, we aimed to make it easier to understand what Gürpınar intended to say about love which he advocated in his works and to understand what he wanted to convey to the reader. The purpose of this article is to subject and interpret the love issue in Hüseyin Rahmi's novels in a psychological context. The issue of love emerges as an issue that keeps up to date in every period. Novels in which love experiences are processed always appeal to the reader. The author, who wants to make his novel more attractive, presents the novel with a love story, even if the main subject is not direct love. When the best-selling novels, most watched series and movies are examined, it can be said that many of them have a strong love story in their content. Love is part of human life. It is good to fall in love. There is no negative side in fondness, where positive emotions such as respect and love are experienced mutually. The end of the lovers in the novels of Hüseyin Rahmi is often tragic. Love suicide, love captivity, unrequited love, rejection, love abuse are among the topics covered in the works. The author seems to have wanted to draw attention to the dangers of love in his works. Too glorifying or underestimating love can have harmful effects, irreparable consequences. It is a fact that logic is lost in the face of the person who falls in love with. Roma give the impression written based on this principle.